(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
Enhancing graduate teacher employability has become a critical concern for educational institutions and policy-makers globally. This article anchored on three pillars of theory, thermostatic principles and mathematical predictions explored the development of an employability framework to improve the career prospects of graduate teachers. Further, the system approach, transformative, human capital and the skills development theories were intergrated into the early developments of the framework. Both the principles of an electric thermostatic properties and the transformative equation were used to strengthen the relevancy of the framework. By integrating these competencies into teacher education programs, the study advocates for a transformative and holistic approach that not only focuses on academic knowledge but also on practical skills and personal attributes. Grounded theory was used as the study methodology to develop an employability thermostatic framework that has capabilities to sense, regulate, control and give relevant feedback. Further, this article navigates through the process of developing the framework which documented a great tool that revolutionizes graduate teacher employability in the most novel and contemporary manner. The employability thermostatic framework offers a structured model for evaluating and enhancing graduate teachers’ readiness for the robust employability. Through a combination of curriculum reforms, industry partnerships, and professional development opportunities, the framework aims to bridge the gap between academic preparation and job market demands. The findings further suggest that a transformative employability thermostatic framework provides a comprehensive approach in solving the problem of graduate teacher employability on the labour market. This article contributes to the ongoing discourse on teacher employability in the most innovative manner that challenges the traditional measures and approaches.